Peranan Konten Podcast Di Channel Deddy Corbuzier Terhadap Perilaku Subscriber: Studi Kasus Episode “Brigadir A.B.C.D.E...Z Dan Terong Belanda..–Kak Onyot - Misfa Aenunnuri; Renty Yuniarti (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
In recent years, podcasts have become a type of content that is popular with many YouTube users. Deddy Corbuzier is a public figure and also the owner of a well-known YouTube channel which provides podcast content for his followers. Deddy Corbuzier's podcast content entitled SOMASI (Stand On Mic Take It Easy) presents standup comedians as guest stars to convey people's complaints about government policies which are packaged casually and funny so that they are easy for subscribers to understand. In this context, content that discusses government policy is predicted to influence a certain point of view for the audience so that in the current research context the focus and aim is to determine the influence of the role of podcast content on Deddy Corbuzier's channel on subscriber behavior in determining the pros and cons of government policy. This research uses a quantitative approach using descriptive methods used in the current study. Data collection techniques are carried out online with the help of Google Forms while data management techniques use Validity Tests and Reliability Tests while data analysis will be carried out using simple Linear Analysis techniques using IBM SPSS 26 software. The results of this research prove that the Ha hypothesis is accepted and Ho is rejected in the current research context. In other words, there is an influence on the role of podcast content on Deddy Corbuzier's channel on subscriber behavior in determining the pros and cons of government policy